Chemotaxonomic distinction of selected closely related Acacia species using chemical properties of their gum exudates - Mhinzi , GS (Tanzania Journal of Science, 2021)
Although Acacia senega var. senegal and Acacia senegal var. leiorhachis are regarded as being closely related botanically, their gum exudates have shown to possess different properties. The properties of the gum exudate from A. senegal var leiorhachis differ from that obtained from A. senegal var. senegal (widely accepted as the source of commercial gum arabic) by being much more viscous, less acidic and having higher proportions of insoluble gel fraction and nitrogen contents. The specific optical rotation values of the gum exudates from these two species have also been found to be different. It is proposed that some of the physicochemical properties of the plant's gum exudates should be included in their taxonomic descriptions to provide an unambiguous distinction of the species. The properties of the gum exudates from A. sieberana var. woodii and A. sieberana var. sieberana, which are also considered to be closely related botanically are similar and it is justifiable to retain them as variants of the same species.